Inelastic collisions in radiofrequency-dressed mixtures of ultracold atoms - Elliot Bentine; Adam J. Barker; Kathrin Luksch; Shinichi Sunami; Tiffany L. Harte; Ben Yuen; Christopher J. Foot; Daniel J. Owens; Jeremy M. Hutson (Physical Review Research, 2020)
Radiofrequency (rf) -dressed potentials are a promising technique for manipulating atomic mixtures, but so far little work has been undertaken to understand the collisions of atoms held within these traps. In this paper, we dress a mixture of ^{85}Rb and ^{87}Rb with rf radiation, characterize the inelastic loss that occurs, and demonstrate species-selective manipulations. Our measurements show the loss is caused by two-body ^{87}Rb+^{85}Rb collisions, and we show the inelastic rate coefficient varies with detuning from the rf resonance. We explain our observations using quantum scattering calculations, which give reasonable agreement with the measurements. The calculations consider magnetic fields both perpendicular to the plane of rf polarization and tilted with respect to it. Our findings have important consequences for future experiments that dress mixtures with rf fields.